History and Prospects of a Journal Devoted to Language Arts - Gapper, Sherry E. (2021)
A systematic account is provided of an academic initiative of the School of Languages and Literatures (Universidad Nacional, Costa Rica): the establishment, publication and maintenance of the journal Letras, founded in 1979. Reference is made to an experience which in time went beyond publishing on literature and linguistics; a description is provided of what has been achieved with the participation of many throughout the years; attention is also given to what can be achieved in the future, when conceived as a permanent projection of university action.